2020
DOI: 10.7861/clinmed.2019-0504
|View full text |Cite
|
Sign up to set email alerts
|

Lessons of the month 4: Giant cell arteritis with normal inflammatory markers and isolated oculomotor nerve palsy

Abstract: Giant cell arteritis (GCA) is an important condition to suspect and treat early, as failure to do so can result in anterior ischaemic optic neuropathy and subsequent permanent visual loss. A 71-year-old woman presented to her local emergency department with a 1-week history of constant, moderatesevere global headache associated with intermittent periorbital pain. Two weeks later she developed sudden horizontal diplopia. Examination demonstrated right oculomotor nerve palsy. Her erythrocyte sedimentation rate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…The thickness of the aorta was significantly higher than that of the control group, the wall of the temporal artery was thickened, the lumen was significantly narrowed, there was much mononuclear cell infiltration in the temporal artery, and the phenomenon of a fullthickness crack appeared. These characteristics indicated that the nude mice in the experimental group showed symptoms of inflammatory damage and increased inflammatory cells, which was consistent with the current results of GCA biopsy [12], which fully illustrated the success of the construction of the GCA animal model in this study. The clinical diagnosis of superficial temporal artery GCA mainly depends on arterial angiography and biopsy [13].…”
Section: Discussionsupporting
confidence: 90%
“…The thickness of the aorta was significantly higher than that of the control group, the wall of the temporal artery was thickened, the lumen was significantly narrowed, there was much mononuclear cell infiltration in the temporal artery, and the phenomenon of a fullthickness crack appeared. These characteristics indicated that the nude mice in the experimental group showed symptoms of inflammatory damage and increased inflammatory cells, which was consistent with the current results of GCA biopsy [12], which fully illustrated the success of the construction of the GCA animal model in this study. The clinical diagnosis of superficial temporal artery GCA mainly depends on arterial angiography and biopsy [13].…”
Section: Discussionsupporting
confidence: 90%
“…It is estimated that about 4% of GCA patients may have normal CRP and ESR, but those with normal inflammatory markers may actually have more prominent PMR symptoms and fewer systemic symptoms [8]. Although our patient consistently had a normal CRP, ESR and platelet count throughout the course of the disease, the temporal artery biopsy confirmed the diagnosis of GCA, which supports a body of evidence [9][10][11][12] suggesting that normal inflammatory markers should not exclude a diagnosis of GCA and PMR [13] . Clinical evaluation for any disease is very important.…”
Section: Discussionsupporting
confidence: 66%
“…Temporal artery biopsy is considered the gold standard; however, it has a sensitivity of only 15–40% [ 4 ]. About 25% of biopsies do not show granulomas [ 3 ] as demonstrated in our patient above.…”
Section: Discussionmentioning
confidence: 53%
“…Though there have been some reports in the literature of Horner’s syndrome in GCA [ 2 , 7 ], pupil-sparing isolated third nerve palsies were only noted twice [ 8 , 9 ] The pathogenesis behind ptosis or Horner’s syndrome remains obscure, likely due to the rarity of this manifestation; however, evidence points to muscle ischemia as the cause behind the visual compromise. In an autopsy done of a patient with ophthalmoplegia secondary to GCA, the extraocular muscles were noted to be necrosed [ 2 , 3 ], suggesting that GCA contributes to internal and external carotid artery ischemia and, subsequently, muscle ischemia and necrosis. There are no data on the effect of Horner’s syndrome or isolated third nerve palsies on the prognosis of visual loss in GCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation